2022
DOI: 10.1017/s1431927622000368
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Digestive Tract of the Little Owl, Athene noctua: Anatomical, Histological, and Scanning Electron Microscopical Studies

Abstract: The digestive tract of the little owl, Athene noctua (Strigiformes: Strigidae), is described in two different seasons. The digestive tract of this bird follows the basic model for that of a predatory bird. The cervical esophagus is not expanded to form a crop. The internal surface of the esophagus forms numerous longitudinal folds provided with numerous mucous glands. These longitudinal folds increase in number and vary in depth posteriorly. The folds of the proventriculus are composed of simple branched tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…The present findings revealed that the oesophagus of the quail was divided into three parts; cervical, crop and thoracic parts similar to those reported in quails (Wilkinson et al, 2018;Zaher et al, 2012), common quail (Parchami & Dehkordi, 2011, rock doves (Shawki et al, 2021), Eurasian collared doves (El-Mansi et al, 2021), homing pigeon (Kadhim & Mohamed, 2015), guinea fowl (Gosomji et al, 2016), geese (Shehan, 2012), Grey-Backed Shrike (Zhu, 2015), partridge (Rossi et al, 2006) and white stork (Rus et al, 2000). In contrast, the oesophagus of captive bustards (Bailey et al, 1997), rheas (Rodrigues et al, 2012 and white-breasted kingfisher (Al Kinany, 2017) consists of two parts; cervical and thoracic, with no crop.…”
Section: Discussionsupporting
confidence: 88%
“…The present findings revealed that the oesophagus of the quail was divided into three parts; cervical, crop and thoracic parts similar to those reported in quails (Wilkinson et al, 2018;Zaher et al, 2012), common quail (Parchami & Dehkordi, 2011, rock doves (Shawki et al, 2021), Eurasian collared doves (El-Mansi et al, 2021), homing pigeon (Kadhim & Mohamed, 2015), guinea fowl (Gosomji et al, 2016), geese (Shehan, 2012), Grey-Backed Shrike (Zhu, 2015), partridge (Rossi et al, 2006) and white stork (Rus et al, 2000). In contrast, the oesophagus of captive bustards (Bailey et al, 1997), rheas (Rodrigues et al, 2012 and white-breasted kingfisher (Al Kinany, 2017) consists of two parts; cervical and thoracic, with no crop.…”
Section: Discussionsupporting
confidence: 88%
“…Their number was found to increase in the intestine of moorhen on moving from the duodenum towards the rectum. A similar distribution pattern for goblet cells has also been recorded in common quail [ 43 ] and little owl [ 34 ]. The high number of goblet cells together with the relatively thicker tunica muscularis of the rectum probably act to facilitate the passage of undigested food to the exterior.…”
Section: Discussionsupporting
confidence: 77%
“…Differing from the studied species, the esophagus of several avian species including chicken, turkey, quail, pigeon, and dove forms a crop that is used by these birds to store and moisten food prior to its digestion [ 32 ]. A number of birds especially those of carnivorous feeding behavior including kestrel [ 33 ] and owl [ 34 ] have been reported to lack the crop. The crop`s functions in the latter Aves have been suggested to be taken over by the esophagus itself [ 35 ].…”
Section: Discussionmentioning
confidence: 99%